What Does “Good” Community and Public Engagement Look Like? Developing Relationships With Community Members in Global Health Research - Hickey, Gary; Porter, Katie; Tembo, Doreen; Rennard, Una; Tholanah, Martha; Beresford, Peter; Chandler, David; Chimbari, Moses; Coldham, Tina; Dikomitis, Lisa; Dziro, Biggy; Ekiikina, Peter O.; et al. (Frontiers in Public Health, 2022)
Community and public engagement (CPE) is increasingly becoming a key component in global health research. The National Institute for Health Research (NIHR) is one of the leading funders in the UK of global health research and requires a robust CPE element in the research it funds, along with CPE monitoring and evaluation. But what does ‘good’ CPE look like? And what factors facilitate or inhibit good CPE? Addressing these questions would help ensure clarity of expectations of award holders, and inform effective monitoring frameworks and the development of guidance. The work reported upon here builds on existing guidance and is a first step in trying to identify the key components of what ‘good’ CPE looks like, which can be used for all approaches to global health research and in a range of different settings and contexts. This article draws on data collected as part of an evaluation of CPE by 53 NIHR-funded award holders to provide insights on CPE practice in global health research. This data was then debated, developed and refined by a group of researchers, CPE specialists and public contributors to explore what ‘good’ CPE looks like, and the barriers and facilitators to good CPE. A key finding was the importance, for some research, of investing in and developing long term relationships with communities, perhaps beyond the life cycle of a project; this was regarded as crucial to the development of trust, addressing power differentials and ensuring the legacy of the research was of benefit to the community.